A survey of the trans-regulatory landscape for Drosophila melanogaster abdominal pigmentation. - Rogers, W.A.; Grover, S.; Stringer, S.J.; Parks, J.; Rebeiz, M.; Williams, T.M. (Developmental Biology, 2014)
Trait development results from the collaboration of genes interconnected in hierarchical networks that control which genes are activated during the progression of development. While networks are understood to change over developmental time, the alterations that occur over evolutionary times are much less clear. A multitude of transcription factors and a far greater number of linkages between transcription factors and cis-regulatory elements (CREs) have been found to structure well-characterized networks, but the best understood networks control traits that are deeply conserved. Fruit fly abdominal pigmentation may represent an optimal setting to study network evolution, as this trait diversified over short evolutionary time spans. However, the current understanding of the underlying network includes a small set of transcription factor genes. Here, we greatly expand this network through an RNAi-screen of 558 transcription factors. We identified 28 genes, including previously implicated abd-A, Abd-B, bab1, bab2, dsx, exd, hth, and jing, as well as 20 novel factors with uncharacterized roles in pigmentation development. These include genes which promote pigmentation, suppress pigmentation, and some that have either male- or female-limited effects. We show that many of these transcription factors control the reciprocal expression of two key pigmentation enzymes, whereas a subset controls the expression of key factors in a female-specific circuit. We found the pupal Abd-A expression pattern was conserved between species with divergent pigmentation, indicating diversity resulted from changes to other loci. Collectively, these results reveal a greater complexity of the pigmentation network, presenting numerous opportunities to map transcription factor-CRE interactions that structure trait development and numerous candidate loci to investigate as potential targets of evolution.